Scholars’ perception about hospitalization: contributions for nursing care - Lapa, Danielle de Freitas; Souza, Tania Vignuda de (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to describe scholars' feelings in terms of hospitalization, and discuss on their perception about hospitalization. It is a qualitative study performed using semi-structured interviews and recordings based on the following atopic for analysis: feelings and perceptions reported by scholars during hospitalization. It was found that the feelings reported by scholars during hospitalization are those of restriction, fear, pain, preoccupation, missing home and others, and anxiety. Most scholars see hospitalization as something negative, though they also report positive aspects such as receiving exclusive affection from their mothers, having access to foods they usually do not have at home and compensations they receive for being ill. Playing emerged as an important activity that alleviates the negative aspects of hospitalization. In conclusion, despite having negative feelings, scholars are able to realize that hospitalization is important for their recovery.